2014
DOI: 10.18268/bsgm2014v66n3a9
|View full text |Cite
|
Sign up to set email alerts
|

Inland dunes fauna and flora from Paleolake Irritila in the Comarca Lagunera, Coahuila, northern Mexico

Abstract: For over a decade the Chihuahuan Desert has been considered as a hotspot of biodiversity. The diverse aquatic ecosystems, especially, are (and were) rich in mollusk species. The dunes of the Comarca Lagunera, Coahuila, Mexico, are of major importance due to the well-preserved remains of animals and plants in a paleolake that covered a vast area in the region. This paper is the first report of the paleolimnological investigations of the Paleolake Irritila ecosystems in northern Mexico. We determined more than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
1
15
0
5
Order By: Relevance
“…from Late Quaternary Paleo-Lake Irritilian Coahuila do not belong to this genus but to the sister genus Cincinnatia Pilsbry, 1891. The only Late Holocene record of Pyrgulopsis, P. manantiali (Hershler), was recently described by Czaja et al (2014b). In sediments of two recently dried-up springs near the town of Viesca, Coahuila, specimens of two species of the genus Pyrgulopsis Call and Pilsbry, 1886 were collected.…”
Section: Introductionmentioning
confidence: 99%
“…from Late Quaternary Paleo-Lake Irritilian Coahuila do not belong to this genus but to the sister genus Cincinnatia Pilsbry, 1891. The only Late Holocene record of Pyrgulopsis, P. manantiali (Hershler), was recently described by Czaja et al (2014b). In sediments of two recently dried-up springs near the town of Viesca, Coahuila, specimens of two species of the genus Pyrgulopsis Call and Pilsbry, 1886 were collected.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the historic biogeography of A. coahuilense. It has already been documented that species is hydrochoric [5], and its principal method of dispersion was through extinct paleolithic lakes and rivers of the Pleistocene [52,53]. Likewise, it is possible to indicate that the occupation of new climatic niches by A. coahuilense occurs over thousands or millions of years.…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez-Salas et al (2014) also found that 70% of A. capricorne seeds showed buoyancy for more than 30 days and that most of the seedlings that developed on the water during the evaluation, also floated. The probable adaptation for dispersion by water currents in A. coahuilense seeds could be considered to explain the geographical range of this plant, which in turn borders the margins of the great Irritila paleolake (Czaja et al, 2014). Taking into account that this area was covered by extensive paleolakes and paleorivers in the past (Van Devender, 1977;Van Devender y Burgess, 1985;Metcalfe, 2006, Marín y Torres-Ruata, 1990) that could have served as a mechanism of dispersion and probably as an agent for deposition of seeds on the limestone hills with rosette vegetation, characteristics where its main nurse Agave lecheguilla inhabits (Muro-Pérez et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Astrophytum coahuilense (considered a different species to A. myriostigma según Vazquez-Lobo et al 2015) is an endemic cactus species native to Mexico and it is currently in vulnerable (VU) category according to the IUCN (2011), mainly due to systematic extraction and habitat destruction in areas where it grows naturally. Various studies propose that the seed of this species is hydrochorous and that it is dispersed by means of water currents (Bregman 1988;Barthlott and Hunt 2000;Sánchez-Salas et al 2012, 2013, which has probably provided a wide range of dispersion to the species along the northern Mexican Chihuahuan desert, considering that in the past (Pleistocene-Holocene) there were abundant paleo-lakes and paleorivers in the north of Mexico (Van Devender y Burgess, 1977, 1985y Marín y Torres-Ruata, 1990;Metcalfe 2006;Czaja et al, 2014). However, there has not been any analysis carried out to show that the structure of the seed together with its density, as adaptations of its empty chambers and spongy tissue, confer buoyancy and to answer the question: why floats the seed of A. coahuilense?…”
Section: Introductionmentioning
confidence: 99%